Brazilian adolescents’ oral health trends since 1986: an epidemiological observational study - Saintrain, Maria Vieira de Lima (BMC Res Notes, 2015)
BACKGROUND: Oral health is part of general health, and in adolescence, it represents a good individual health indicator. Three country-based oral health epidemiological studies have been developed in Brazil (1986, 2003 and 2010). The objective of this study was to analyze oral disease trends among Brazilian adolescents and to compare these trends to the World Health Organization’s goals with a focus on public health policies implemented between 1986 and 2010. METHODS: This is an epidemiological observational study performed with secondary data from Brazilian Oral Health surveys (1986, 2003 and 2010). The DMFT (number of decayed, missing and filled teeth) index was used for the 12-year-old and 15- to 19-year-old groups, and periodontal disease (CPI) and the percentage of individuals who needed and/or had prostheses were evaluated in the 15- to 19-year-old group. RESULTS: Between 1986 and 2010, DMFT decreased from 6.65 to 2.07 (68.9 % reduction) in the 12-year-old group and from 12.68 to 4.25 (66.5 % reduction) in the 15- to 19-year-old group. In all groups, the missing component had the strongest decrease. Adolescents had a reduction of 20.3 % in access to dental care. In 2003, in the 15- to 19-year-old group, 89.5 % of teenagers had at least one decayed tooth, while in 2010, the value was 76.1 %. In 2010, the percentage of adolescents without gingival problems varied among different regions of Brazil, with 30.8 % in the North and 56.8 % in the Southeast. Regarding DMFT, the difference between the North and Southeast Regions was 84 %. CONCLUSIONS: Improvement trends regarding adolescent oral health were observed, which seem to be supported by health education and promotion activities along with the reorganization of the Brazilian health system.